Selection of high yielding and anthracnose resistant Stylosanthes for Brazil, India and China - White, N.; Chakraborty, S.; Fernandes, C.D.; Charchar, Maria José; Melkania, NP; Ramesh, CR; Gangaiah, B; Guodao, L; Cameron, DF; Miles, John W. (Canadian Forage Council, 1997)
Resistance to anthracnose, dry matter yield (DMY) and seed yield (SY) was assessed for germplasm and breeding lines of Stylosanthes in Brazil, India and China. Overall, Stylosanthes guianensis produced higher D MY than S. scabra, S. capitata and S. macrocephala at most sites in Brazil. Data from China suggest that there are high yielding anthracnose resistant S. guianensis lines that can reduce the reliance on CIAT 184. S. seabrana might also prove successful. S. seabrana in India produced the highest D MY and SY and it can form nodules with native Bradyrhizobium strains. Regional differences in resistance within accessions stress the importance of targeting germplasm to combat the suite of pathogen races present at a local level.